Implementation of Rahn and Murabahah Agreements at KSPPS BMT NU East Java Mayang Jember Branch - Falahuddin, Moh. Arif; Kamil, Ahmad; Rahman, Fadali (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
Rahn and murabahah are one of the financing products at KSPPS BMT NU which aims to increase financial inclusion and community economic empowerment. This research explores the implementation of Rahn and murabahah in BMT NU with a focus on the process and its impact on community economic development. The research method used is a qualitative approach through in-depth interviews with BMT managers and analysis of related documentation. The research results show that of the several contracts in KSPPS BMT NU, two of them are the community's favorite products, namely rahn and murabahah, which have been successfully implemented by prioritizing the principles of justice, transparency and active member participation. This financing has had a positive impact in increasing financial access, helping the development of usaha mikro, kecil, menengah (UMKM), and strengthening the community's economy. The implications of this research provide an important contribution in understanding the role of KSPPS BMT NU in advancing an inclusive and sustainable economy at the local level.